Morphometric characterization and land use and cover of a microbasin in the city of Buri, SP - Nogueira, Felipe; Ferreira, Marcos Paulo; Tonello, Kelly Cristina (Revista Hipótese, 2020)
This study aims to analyze the microbasin morphometry of a tributary of the Apiaí-Guaçu River, located in the city of Buri, SP, one of the priority areas for the conservation of plants and water resources. The morphometric characteristics were obtained through the relief, geometric and drainage parameters. The land use and land cover mapping, as well as the microbasin delimitation were obtained through the use of Qgis software, 2.14.2. According to the microbasin morphometry, it is possible to observe that it has a low drainage capacity, low runoff and greater water infiltration. The microbasin relief is disconnecting itself from agriculture, silviculture and pasture, with the native forest located in the permanent preservation areas.
Keywords: Morphometry; Watershed; Buri-SP